Centralized charging station planning for battery electric trucks considering the impacts on electricity distribution systems - Bo Li; Dekai Jing; Haiwang Zhong; Gang He; Ziming Ma; Guangchun Ruan; Minyou Chen; Daniel M. Kammen (Energy Reports, 2023)
To address environmental challenges resulting from transportation sector’s carbon emissions, replacing conventional internal combustion engine vehicles with electric vehicles is a key solution. Comprehensive electrification of heavy-duty trucks can promote the decarbonization of the freight transportation. The mismatch of supporting infrastructures is one of the major barriers to the deployment of battery-electric trucks (BET). BET charging behaviors and vehicle daily operations could influence the charging station planning and electricity distribution systems, which will cause the costs of upgrading distribution grid. This paper studies centralized BET charging station planning, considering the impacts of plug-in fast charging mode on the distribution systems. First, the BET model is proposed to capture BETs charging load profiles based on real-world operating data. Then, a mixed-integer programming model is formulated for charging station planning considering the upgrade requirements for distribution systems based on the BET model. After the co-optimization of centralized charging station planning and charging strategies of BET, the size of charging stations and charging schedules are determined. The results of numerical experiments indicate that charging demand from 50 BET can be met at current charging infrastructure technologies (>60 kW per charger) with a 37% reduction in the upgrade of distribution systems if incorporating managed charging strategy.